Pd-Au Electrocatalysts for Hydrogen Evolution Reaction at Neutral pH - Elitsa Chorbadzhiyska; Mario Mitov; Georgi Hristov; Nina Dimcheva; Lori Nalbandian; Antigoni Evdou; Yolina Hubenova (International Journal of Electrochemistry)
Pd-Au codeposits with different ratio of both metals were electrodeposited on carbon felt, characterized by scanning electron microscopy, and investigated as electrocatalysts towards hydrogen evolution reaction in neutral phosphate buffer solution. The quantities of the produced hydrogen gas with different electrocatalysts, estimated from data obtained by chronoamperometry, were confirmed by mass spectrometry analysis. The highest hydrogen evolution rate was achieved with the electrocatalysts, produced from electrolyte with equal Pd and Au content.